Utilizing Papal Taxation Records for Geographical, Economic, and Cultural Analysis: A Study of Early Fourteenth Century Ireland - CHEVALLIER, CHRISTOPHER (Trinity College Dublin. School of Natural Sciences. Discipline of Geography, 2020)
This project explores the economic, physical, political, and cultural geography of medieval Ireland by mapping the 1302-20 papal tax valuations of ecclesiastical benefices, with parish incomes being used as proxies for local economies. Doing so addresses a lack of uniform, island-wide, and fine-tuned economic data for medieval Ireland. These valuations were ascertained for the purposes of papal tenth, or decime, taxations and offer a unique and invaluable look into the landscape of medieval Ireland that transcends cultural boundaries. An initial step of this project was to clarify the details and nuances behind papal taxation, as well as papal finances specifically in Ireland. For this task, fieldwork was undertaken at the Vatican Secret Archives, the Archives Nationales (Paris), and the British National Archives (Kew) to evaluate documents regarding how and when valuations for papal tenths were made. Outside of this, these trips were undertaken to search for additional Irish valuations and identify analogous documents that could be employed for future studies and comparison. The 1302-20 sources themselves required analysis and clarification regarding their dating and contents. The main effort of this thesis was to elucidate the modern locations behind the medieval parish placenames within the 1302-20 valuations. Many of the placenames were unidentified or contested due to the nature of their transcription (i.e. English and or Latin speaking clerks writing down Irish language placenames phonetically). Once this task was complete, the exact, or very proximate, coordinates of the corresponding medieval churches were obtained to create a geodatabase. The produced maps reveal the distribution of wealth of medieval Ireland at local, regional, and national scales, as well as illustrate the extent of English colonisation. Additionally, the valuations were combined with additional data, such as soil fertility, land slope, elevation, and archaeological records to perform quantitative analysis within the GIS. From the maps and analyses, insights were made regarding medieval Ireland's landscapes, cultures, and polities. The English colony was largely defined by cambisol and luvisol soils, as well as flat lowland terrain. Within the colony, access to commercial networks and proximity to urban sites were leading factors in explaining wealth distribution. Gaelic lordships often contended with environmental and commercial marginalisation but proved resilient. The analysis suggests that Gaelic economies were based on pastoralism, bartering, and billeting, producing only low-surpluses. However, these economies were adaptable to conflict and able to provide Gaelic lords with the resources to field armies and resist colonial intrigue. Political analysis and discussions regarding the colony's extent suggest that the degree of English domination over Ireland has been overstated. The chronology of the sources used enables a measurement of the economic impact of the Great European Famine (1315-17) and Bruce Invasion (1315-18). Pre-war valuations were compared with their post-war counterparts to assess changes at a parish and diocesan level. In addition to this, commentary was provided on the events of the Bruce Invasion and how the devastation it caused impacted the colony in the long term. This research has produced a baseline from which to evaluate the medieval Irish economy and peak of the medieval English colony, as well as a database that can allow future studies regarding Irish economics and geography. It must be noted that this project also addressed major gaps in Irish history and is the first monograph devoted to the utilised sources (though not the first to utilise or discuss them). The work concludes with comparative maps of English, Welsh, and French/Swiss dioceses, highlighting the potential of this type of source and their validity for geographical analysis. Additionally, suggestions were provided for future studies, as well as further work related to the maps produced by this research and the 1302-20 valuations.
APPROVED
Keywords: geography; papal taxation; papal valuations; medieval history; GIS; medieval Ireland; Bruce Invasion; Great European Famine; distribution of wealth; economic history; Robert the Bruce; Edward Bruce; Gaelic Ireland; Vatican; Anglo-Norman; Normans; medieval England; medieval France; Philip the Fair; Irish history; mapping; Irish landscapes; demographics; medieval records; colonization; pastoral; medieval politics